1999
DOI: 10.1007/s004330050129
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and oedema in experimental brain injury: comparison of treatment with methylprednisolone, tirilazad mesylate and vitamin E

Abstract: Trauma-induced lipid peroxidation (LP) is one of the most important factors that produces tissue damage in head trauma. In the present study, the protective effects of free radical suppression with methylprednisolone (MP), tirilazad mesylate (TM) and vitamin E on the development of cerebral LP and oedema resulting from head trauma have been investigated. Rats were divided randomly into four groups. Bolus injections of physiological saline, MP (initial 30 mg/kg for 1 h, continuing administration of 5.4 mg/kg pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Alpha tocopherol reduced microscopic brain damage and also promoted nerve regeneration probably by reducing Nogo-A and NgR expression [ 320 ]. Although these behavioral effects are important, a study showed limited efficacy of vitamin E on lipid peroxidation in the acute post-injury phase [ 321 ]; others have demonstrated a later improvement in markers of oxidative stress. Vitamin E could also present neuroprotective effects for TBI associated dementia [ 322 ].…”
Section: Vitamin Supplementationmentioning
confidence: 99%
“…Alpha tocopherol reduced microscopic brain damage and also promoted nerve regeneration probably by reducing Nogo-A and NgR expression [ 320 ]. Although these behavioral effects are important, a study showed limited efficacy of vitamin E on lipid peroxidation in the acute post-injury phase [ 321 ]; others have demonstrated a later improvement in markers of oxidative stress. Vitamin E could also present neuroprotective effects for TBI associated dementia [ 322 ].…”
Section: Vitamin Supplementationmentioning
confidence: 99%
“…Treatment with vitamin E is effective for some forms of cancer, and prevents and repairs cell tissue damage following radiation [169]. In the central nervous system it has been investigated under lesion [176] and TBI models [31,101]. The neuroprotective effects of α-T are primarily mediated by its prevention of free radical propagation via the halting of polyunsaturated fatty acid oxidation chain reactions [20,167].…”
Section: Vitaminsmentioning
confidence: 99%
“…Furthermore, vitamin E reduces amyloidosis and improves cognitive function after repetitive TBI in a model of Alzheimer’s disease [33]. Although these behavioral effects are substantial, one study has shown limited efficacy of vitamin E on lipid peroxidation in the acute post-injury phase [101], but others have highlighted improvements in markers of oxidative stress at later time points [93,167]. Additional studies have demonstrated that extended pretreatment confers the strongest reductions in lipid peroxidation and oxidative stress [55,209].…”
Section: Vitaminsmentioning
confidence: 99%